2016
DOI: 10.1111/ijfs.13042
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Chinese noodle quality by supplementation with arabinoxylans from wheat bran

Abstract: Summary This study was performed to investigate the effects of arabinoxylans on Chinese noodles quality. Unmodified arabinoxylans (UAX) and modified arabinoxylans (MAX) were added to wheat flour at 0.25–2.0% (w/w), and noodle samples were evaluated in terms of colour, free sulfhydryl groups, disulphide bond, water, texture properties and cooking characteristics. As the amounts of arabinoxylans increased, dough sheet became darker, and the texture of the cooked noodles increased and then deteriorated after 1% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…The relaxation time of T 21 , T 22 , and T 23 of TBN were significantly smaller compared to CN (Table ) which indicated the closer integration of the water and macromolecules such as protein and starch . Similar results were reported by Fan et al As Tartary buckwheat incorporation increased, T 21 , T 22 , and T 23 decreased.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The relaxation time of T 21 , T 22 , and T 23 of TBN were significantly smaller compared to CN (Table ) which indicated the closer integration of the water and macromolecules such as protein and starch . Similar results were reported by Fan et al As Tartary buckwheat incorporation increased, T 21 , T 22 , and T 23 decreased.…”
Section: Resultssupporting
confidence: 81%
“…The distance of CN and TBN decreased significantly with further addition. Similar results have been reported by Fan et al [31] Addition of dietary fiber could result in a decrease in maximal breaking force and distance. Moreover, high gluten content could also reduce the elastic ability of noodles.…”
Section: Effect Of Tartary Buckwheat On Texture Analysis Of Noodlessupporting
confidence: 91%
“…Numerous studies have revealed that the addition of DFs is more likely to produce doughs with harder texture and less springiness (Bleis et al, 2015;Wang et al, 2017a,b). Studies have indicated that the interactions among gluten, starch and DFs may be one of the major factors responsible for the quality of the flour product (Abang Zaidel et al, 2008;Chen et al, 2011;Fan et al, 2016). It has also been established that the bread quality is directly linked with the gluten conformation and aggregation properties, as significant correlations have been found between gluten macropolymer quantity and the rheological properties of dough (Wang et al, 2007;Nawrocka et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With increased storage time, the binding force between starch and the gluten network structure in fresh wet noodles weakened gradually. Subsequently, the dissolution of starch in the cooking process increased, leading to a gradual increase of cooking loss rate and a decrease of water absorption rate as storage time increased [16]. e water absorption rate of 1S presented the opposite trend under different storage temperatures.…”
Section: Textural Properties As Shown Inmentioning
confidence: 98%
“…Fresh wet noodles were prepared as described previously [16]. Briefly, 100 parts of wheat flour and 35 parts of deionized water were mixed for 7 min using a pin mixer.…”
Section: Noodle Preparationmentioning
confidence: 99%